2021
DOI: 10.3837/tiis.2021.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Using Online Information Support to Decrease Stress, Anxiety, and Depression

Abstract: Today, online education is becoming more important. The effectiveness of online education has been measured by student satisfaction and the possibility of substituting offline education. This study proposes a plan to increase the effectiveness of education in a new form by using online information. Education is the process of socializing and growing learners. Representative negative emotions experienced by learners are stress, anxiety, and depression (SAD). A reduction in SAD will promote student growth and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…CR for exploitative leadership, psychological distress, leader's incivility, playing dumb, evasive hiding, rationalized hiding, and procrastination was all higher than 0.7. Overall, the value of AVE and CR satisfied acceptable requirements (Jin and Hahm, 2021;Jin et al, 2022). Thus, all measurements had significant validity.…”
Section: Confirmatory Factor Analysis and Validity Analysismentioning
confidence: 58%
See 1 more Smart Citation
“…CR for exploitative leadership, psychological distress, leader's incivility, playing dumb, evasive hiding, rationalized hiding, and procrastination was all higher than 0.7. Overall, the value of AVE and CR satisfied acceptable requirements (Jin and Hahm, 2021;Jin et al, 2022). Thus, all measurements had significant validity.…”
Section: Confirmatory Factor Analysis and Validity Analysismentioning
confidence: 58%
“…As shown, the research model showed a good fit for our data with X 2 (p) = 2359.159(0.000), X 2 /df = 2.595, RMSEA = 0.075, IFI = 0.902, CFI = 0.901, PGFI = 0.630, and PNFI = 0.780. These indices satisfy the acceptable requirement (Jin and Hahm, 2021;Jin et al, 2022). Moreover, the standardized regression weights of exploitative leadership, psychological distress, leader's incivility, playing dumb, The research model.…”
Section: Confirmatory Factor Analysis and Validity Analysismentioning
confidence: 96%
“…Previous research has already been conducted on measures to reduce depression, anxiety, and stress. In particular, Jin and Hahm (2021) demonstrated how support can reduce depression, anxiety, and stress. Future studies should focus on finding ways to enhance the psychological health of workers.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…One foreseeable situation in the near future is an increase in online-based communication. Advances in technologies such as AI, big data, and IoT, and online experiences such as online-based lectures and meetings will expand the use of online communication [3,4]. In particular, companies will use online-based information sharing through cloud computing, virtual team, and online-based meetings.…”
Section: Introductionmentioning
confidence: 99%